ESG pravidla a jejich role v oblasti udržitelnosti finančních trhů - Roman Vybíral (Acta Universitatis Carolinae. Iuridica)
The paper deals with the issue of sustainability, respectively the so-called ESG rules (Environmental, Social and Corporate Governance rules), with a focus on financial markets. In terms of content, the paper is divided into four main parts, which focus on the relationship between ESG rules and sustainability in financial markets, the role of ESG rules in the existing regulatory framework, the concrete implications of ESG rules in financial markets, and the impact of new ESG rules on financial markets. The first part will define the interrelationship between ESG rules and the concept of sustainability and describe the meaning and role of both concepts. The second part will examine the position of ESG rules in the current financial market regulation, including an analysis of the role of ESG rules. The next part will describe the specific main legislation currently incorporating ESG rules into practice of European and domestic financial market. The fourth chapter will address the anticipated or known impacts of existing ESG rules on financial market practice, including the identification of potential strengths and weaknesses. The aim of the paper is to define the role of the new ESG rules in the current regulatory basis of entities operating in the financial markets, then to describe and evaluate the current ESG regulatory framework binding on entities operating in the domestic financial sector and, last but not least, to describe and try to assess the currently presented impacts of these new and gradually introduced rules in the sphere of sustainability of the European and domestic financial market.